2014
DOI: 10.1016/s2214-109x(13)70048-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of different strategies to monitor adults on antiretroviral treatment: a combined analysis of three mathematical models

Abstract: Background The WHO’s 2013 revisions to its Consolidated Guidelines on ARVs will recommend routine viral load monitoring (VLM), rather than clinical or immunological monitoring, as the preferred monitoring approach on the basis of clinical evidence. However, HIV programmes in resource-limited settings require guidance on the most cost-effective use of resources given other competing priorities, including expansion of ART coverage. Here we assess the cost-effectiveness of alternative patient monitoring strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 34 publications
1
45
0
1
Order By: Relevance
“…Global ART scale-up has been made possible by the use of standardized and simplified treatment protocols and decentralized service delivery, with limited reliance on laboratory monitoring [3,4]. In order to enhance treatment monitoring, WHO recommended by 2013 that viral load measurements among people receiving ART be performed 6 months after initiating ART and every 12 months thereafter [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Global ART scale-up has been made possible by the use of standardized and simplified treatment protocols and decentralized service delivery, with limited reliance on laboratory monitoring [3,4]. In order to enhance treatment monitoring, WHO recommended by 2013 that viral load measurements among people receiving ART be performed 6 months after initiating ART and every 12 months thereafter [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent costing studies have concluded that when the benefits of guided regimen switches are considered, viral load monitoring is found to be cost effective and life-saving (Ajose et al, 2012;Kahn et al, 2011). Improving the feasibility and reducing the cost of viral load monitoring are important policy objectives (Keebler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Even though WHO (2013WHO ( , 2014 guidelines recommend routine viral load monitoring, India is not currently recommending routine viral load monitoring (Medecins Sans Frontieres, 2014). The priority for HIV programs should be to expand ART coverage using lower cost clinical or CD4 monitoring (Keebler et al, 2014). Further, as second-line ART has a greater role in the management of HIV infection, the need for evidence to establish the criteria for switching to second-line ART is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Summary results have been presented elsewhere by Eaton and Menzies et al [5] and Keebler and Revill et al [6]. In brief, we estimated that, in programmes with high ART coverage, expanding treatment eligibility to HIV-positive adults with CD4 þ cell counts up to 500 cells/ml or even higher appears to be cost-effective, but this will need to be accompanied by large expansions in HIV testing and a enrolment in care in order to maximize the potential reductions in HIV incidence [5].…”
mentioning
confidence: 81%
“…In brief, we estimated that, in programmes with high ART coverage, expanding treatment eligibility to HIV-positive adults with CD4 þ cell counts up to 500 cells/ml or even higher appears to be cost-effective, but this will need to be accompanied by large expansions in HIV testing and a enrolment in care in order to maximize the potential reductions in HIV incidence [5]. Moreover, although more sophisticated forms of patient monitoring-such as frequent viral load measurement-are expected to confer benefits, expanding ART coverage would be expected to generate greater population health benefits from limited resources [6].…”
mentioning
confidence: 99%